The Effectiveness of Digital Drawing Video Tutorials as Instructional Media - Damayanti, Savira; Widjarnako, Dwi; Na’am, Muh Fakhriun (Universitas Negeri Semarang, 2026)
Students have difficulty understanding the complex techniques of digital drawing without a clear and interactive visual guide. Video tutorials as media are an alternative solution that can provide the visualization in step-by-step and learning flexibility in accordance with students' individual learning pace. This study aims to analyze the effectiveness of video tutorials for using Adobe Illustrator as instructional media. The study used a quasi-experimental design. The subjects of the study were 11th-grade students majoring in Fashion Design at SMK Islam Sudirman 1 Ambarawa, consisting of two classes: XI Tabus 1 with 30 students and X Tabus 2 with 30 students. The techniques for collecting data were a validation sheet from media and material experts, a digital drawing skill test (posttest), and student and teacher questionnaires. Data were analyzed using descriptive statistics and an independent sample t-test to measure the effectiveness of the media. The results of the effectiveness test showed a significant difference in student skills between the experimental and control groups, as reflected in the mean posttest score. The statistical test showed a significance value [0.000] < 0.05, indicating that digital drawing video tutorials as media are effective for students' learning process. Digital drawing video tutorial as a media is feasible, effective, and received positive response from both students and teachers.